A wastewater‐based evaluation of the effectiveness of codeine control measures in Australia. (29th November 2022) - Tscharke, Benjamin J.; O'Brien, Jake W.; Ahmed, Fahad; Nguyen, Lynn; Ghetia, Maulik; Chan, Gary; Thai, Phong; Gerber, Cobus; Bade, Richard; Mueller, Jochen; Thomas, Kevin V.; White, Jason; et al.
Abstract: Background and aim: From 1 February 2018, codeine was rescheduled from an over‐the‐counter (OTC) to a prescription‐only medicine in Australia. We used wastewater‐based epidemiology to measure changes in population codeine consumption before and after rescheduling. Methods: We analysed 3703 wastewater samples from 48 wastewater treatment plants, taken between August 2016 and August 2019. Our samples represented 10.6 million people, 45% of the Australian population in state capitals and regional areas in each state or territory. Codeine concentrations were determined by liquid chromatography–tandem mass spectrometry and converted to per‐capita consumption estimates using the site daily wastewater volume, catchment populations and codeine excretion kinetics. Results: Average per‐capita consumption of codeine decreased by 37% nationally immediately after the rescheduling in February 2018 [95% confidence interval (CI) = 35.3–39.4%] and substantially in all states between 24 and 51% (95% CI = 22.4–27.0% and 41.8–59.4%). The decrease was sustained at the lower level to August 2019. Locations with least pharmacy access decreased by 51% (95% CI = 41.7–61.7%), a greater decrease than 37% observed for those with greater pharmacy access (95% CI = 35.1–39.4%). Regional areas decreased by a smaller margin to cities (32 versus 38%, 95% CI = 30.2–34.1% versus 34.9–40.4%, respectively) from a base per‐capita usage approximately 40% higher than cities. Conclusion: Wastewater analysis shows that codeine consumption in Australia decreased by approximately 37% following its rescheduling as a prescription‐only medicine in 2018. Wastewater‐based epidemiology can be used to evaluate changes in population pharmaceutical consumption in responses to changes in drug scheduling.